If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 1(4) + h Multiply 1 * 4 1 = 4 + h Solving 1 = 4 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 1 + -1h = 4 + h + -1h Combine like terms: h + -1h = 0 1 + -1h = 4 + 0 1 + -1h = 4 Add '-1' to each side of the equation. 1 + -1 + -1h = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -1h = 4 + -1 -1h = 4 + -1 Combine like terms: 4 + -1 = 3 -1h = 3 Divide each side by '-1'. h = -3 Simplifying h = -3
| 64x+2+25x=180 | | 6+3(x+4)=3x+12 | | 4b-(6b-8)= | | H^2+5h=190 | | 4x+4=9-36 | | 40x+5+18x+1=180 | | 4=-4(-5)+h | | 2x+17-7x-6=8-10X-19+5X | | .33x+2=-2 | | 20x=21x-4 | | h=-16t^2+64t+13.5 | | -2=3(2)+h | | (8b-12)+(2b+5)+b=180 | | 98+7x=104+4x | | -2=2(-3)+n | | 9x+11=10x+2 | | 3x+15=-9+7x | | 2=-2(4)+b | | 6n-(3n+8)=16 | | R^2+8r+15= | | 7(n+5)+6(3n+6)=21 | | .33=5-.66x | | 49=-7t+1 | | x+2(-2)=1 | | -30+x=24-5x | | 5z+12-6z+10= | | (8+10i)*(5-8i)= | | -7x+1=7x-1 | | -.75x+.80=.25x-.20 | | -(1+r)=-3-4r | | 2.3x-2=0 | | -25+4x=-x+35 |